Lack of effect of intermittent preventive treatment for malaria in pregnancy and intense drug resistance in western Uganda. (December 2015) - Braun, Vera; Rempis, Eva; Schnack, Alexandra; Decker, Sarah; Rubaihayo, John; Tumwesigye, Nazarius; Theuring, Stefanie; Harms, Gundel; Busingye, Priscilla; Mockenhaupt, Frank
Abstract Background Intermittent preventive treatment in pregnancy (IPTp) with sulfadoxine–pyrimethamine (SP) is widely implemented in sub-Saharan Africa for the prevention of malaria in pregnancy and adverse birth outcomes. However, in areas of intense SP resistance, the efficacy of IPTp may be compromised. Methods A cross-sectional study among 915 delivering women (728 analysable live singleton deliveries) was conducted in Fort Portal, western Uganda, to assess associations of reported IPTp use, Plasmodium falciparum infection, maternal anaemia, low birth weight, and preterm delivery, and to estimate the degree of SP resistance as reflected bypfdhfr/pfdhps mutations. Results Plasmodium falciparum infection was detected by PCR in 8.9 % and by microscopy of placental blood samples in 4.0 %. Infection was significantly associated with stillbirth, early neonatal death, anaemia, low birth weight, and pre-term delivery. Eighty percent of the women had taken at least one dose of IPTp, and more than half had taken two doses. As compared to women without chemoprophylaxis against malaria, IPTp had no significant influence on the presence ofP. falciparum infection (13.8 vs. 9.6 %, P = 0.31). Nor was it associated with reductions in anaemia, low birth weight or preterm delivery.P. falciparum with intense SP resistance (pfdhfr/pfdhps quintuple or sextuple mutations) were observed in 93 % (pfdhps 581G, 36 %), and the additional high resistance allelepfhdr 164L in 36 %. Conclusions In Fort Portal, Uganda, reported use of IPTp with SP does not provide an observable benefit. The molecular markers ofP. falciparum indicate high grade SP resistance reaching the threshold set by WHO for the discontinuation of IPTp with SP. Alternative approaches for the prevention of malaria in pregnancy are urgently needed.